Inside adobe Photoshop 4 - Gary David Bouton (New Riders, 1997)
Exploring features, old and new; Up and running; Image retouching; Advanced imaging; Photoshop special effects; Production, Web-worthy imaging, and beyond; Pulling out all the stops: advanced techniques.